2019
DOI: 10.1136/bmjopen-2018-027531
|View full text |Cite
|
Sign up to set email alerts
|

B!RTH: a mixed-methods survey of audience members’ reflections of a global women’s health arts and science programme in England, Ireland, Scotland and Switzerland

Abstract: ObjectivePublic engagement and science communication are growing as an important forum in the design and dissemination of research. The B!RTH programme is a partnership that uses theatre in combination with scientific expert panel discussions to raise awareness about the global inequality in women’s health and access to healthcare. As part of this project, we assessed the views and experiences of audiences participating in B!RTH events.DesignWe conducted a multi-site mixed-methods survey using paper-based ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(51 citation statements)
references
References 18 publications
(37 reference statements)
0
51
0
Order By: Relevance
“…Key study characteristics are described in Table 1 . Six of the eight included studies were published between 2015 and 2020 [ 36 39 , 41 , 42 ]. Seven of the eight studies used mixed-methods research [ 35 40 , 42 ], with one study using quantitative methods alone [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Key study characteristics are described in Table 1 . Six of the eight included studies were published between 2015 and 2020 [ 36 39 , 41 , 42 ]. Seven of the eight studies used mixed-methods research [ 35 40 , 42 ], with one study using quantitative methods alone [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data extracted on study characteristics showed that the studies which had separate researcher or evaluation teams were of higher methodological quality [ 37 , 38 , 40 42 ]. One study did not explicitly state the relationship between the evaluation and festival teams [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations